Characterization and Optical Studies of Hydroxyethyl Cellulose-Copper Oxide Nanocomposites - Alsubaie, A. S. A. (Journal of Spectroscopy, 2022)
In this study, monometallic copper oxide nanoparticles (CuONPs) were synthesized by chemical reduction of copper sulfate (CuSO4) salt through sugar glucose. X-ray diffraction profiles approved the formation of metallic oxide nanoparticles. TEM images showed spherical nanoparticles with an average particle size of 60 nm. The interaction of HEC and copper oxide nanoparticles was investigated by FTIR spectroscopy. The UV-visible absorption spectrum showed a surface plasmon resonance peak at 270 nm. The effect of doping of copper oxide nanoparticles (CuONPs) on the optical and thermal properties of HEC was studied. The results showed that the concentration of CuO nanoparticles has a prominent influence on the optical, structural, and thermal properties of hydroxyethyl cellulose.